Effects of Acute Recombinant Human TSH on Serum Ghrelin Levels - Ciuoli, Cristina; Brusco, Lucia; Theodoropoulou, Alexandra; Castagna, Maria Grazia; Neri, Ornella; Pasqui, Letizia; Pacini, Furio (Frontiers in Endocrinology, 2011)
Recent findings showed the presence of a reciprocal relationship between thyroid hormones and ghrelin, although the exact mechanism is not known. Design: Our study is addressed to evaluate the effect of acute exogenous rhTSH administration on serum ghrelin levels in athyreotic patients on replacement l-thyroxine therapy. The study group included fifty patients (16 males and 34 females) submitted to total thyroidectomy and 131-iodine remnant ablation for differentiated thyroid cancer on l-thyroxine therapy. Mean age was 47.5 ± 16.5 years and mean BMI was 25.6 ± 5.01 kg/m². rhTSH was administrated at the dosage of 0.9 mg i.m once daily for two consecutive days. Blood samples were taken between 08.00 and 09.00 after a overnight fasting for measurement of TSH, FT3, FT4 and ghrelin before the first administration of rhTSH and for measurement of TSH and ghrelin 24 h, 48 h, 72 h and 96 h after the first administration of rhTSH. Results: Mean ± SD values of basal TSH were 0.54 ± 0.77 µU/ml without significant difference between females and males. As expected, after rhTSH administration TSH concentrations increased at 24 h and 48 h with peak TSH values ranging from 20.20 to 313 µU/ml (mean ± SD 98.4±66.7µU/ml). Mean ± SD values of basal ghrelin were 1085 ± 373 pg/ml without significant difference between males and females. After rhTSH administration ghrelin concentrations decreased significantly (p<0.01) at 24 h (mean ± SD 934 ±314 pg/ml p<0.01) and returned to pre-treatment levels at 96 h. Conclusion: Our study demonstrates that acute exogenous TSH administration has a suppressive effect on ghrelin secretion independent from changes in thyroid status.